Pengembangan Alat Peraga Papan Pelangi pada Operasi Hitung Pecahan di Sekolah Dasar - Yuliani Rahayu (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2018)
Based on mathematics instructional observation result in SDN 7 Lembang West Bandung regency, it founded low condition of mathematics conceptual understanding on fraction material that caused a low students learning outcomes. So that to solve this problem by developing papan pelangi media board. A board that consist of colorful blocks. The aimed of developing this papan pelangi is to increasing students learning outcomes and mathematics conceptual understanding. The leraning innovation development result shows students learning outcomes are arising, before using papan pelangi are in 60,33% rates, then increasing on first implementation to 70,33% and then increasing on second implementation to 82,67% rates. We can conclusing that this achievement is because the using of papan pelangi media where students are active in manipulating papan pelangi as mathematics conceptual understanding.